Molecular diagnosis for Harpophora maydis, the cause of maize late wilt in Israel - DRORI, Ran; SHARON, Amir; GOLDBERG, Doron; RABINOVITZ, Onn; LEVY, Maggie; DEGANI, Ofir (Phytopathologia Mediterranea, 2012)
Late wilt of maize, caused by the fungus Harpophora maydis, is one of the most important fungal diseases in Egypt. The disease has also been reported from India, Hungary, Spain and Portugal. The pathogen survives for long periods in soil. Late wilt is currently controlled using maize varieties with reduced sensitivity, but virulent variants of the fungus may threaten these varieties. Common disease symptoms have been documented over 20 years in Upper Galilee (northern Israel), particularly the Hula Valley. Recently, prevalence of the disease has increased. This is the first confirmed report of the direct and primary cause of the disease in Israel. Isolates of the pathogen obtained from wilting maize plants were morphologically identical to those of strains found in Egypt and India. We modified a molecular method as a diagnostic assay of disease progress in an infested field in northern Israel. The assay identified the pathogen 50 d after seeding, before the emergence of disease symptoms, both in susceptible and partially resistant host plants. DNA assessment was consistent with the disease progress in a susceptible maize variety, and the pathogen also spread in partially resistant plants that showed no symptoms. Seeds of apparently healthy, partially resistant plants may therefore also spread the disease. A modified molecular method presented here is a preliminary step in developing a seed health assay.